Effect of copper on the translocation and transformation of polychlorinated biphenyls in rice. (February 2018) - Pan, Lili; Sun, Jianteng; Le, X. Chris; Zhu, Lizhong
Abstract: Contamination of organic pollutants in the environment is usually accompanied by heavy metals. However, a little information on the influences of heavy metals on the uptake, translocation and transformation of organic pollutants in plants is available. In this study, ten-day hydroponic exposure was conducted to explore the influence of copper (Cu) on the bioaccumulation and biotransformation of polychlorinated biphenyls (PCBs) in intact young rice ( Oryza sativa L.). Low dose of Cu (≤100 μmol/L) increased the accumulation of CB-61 in rice plants, while excess concentrations of Cu (>100 μmol/L) inhibited uptake and translocation of CB-61. Effect of Cu on the uptake of CB-61 was attributed to the Cu-triggered damage to the roots of rice plants. The presence of a moderate dose of Cu (50 μmol/L) enhanced the formation of hydroxylated polychlorinated biphenyls (OH-PCBs) and methoxylated polychlorinated biphenyls (MeO-PCBs), whereas excess concentrations of Cu (250 μmol/L) inhibited the metabolism of CB-61. The effect of Cu on the interconversion between 4′-OH-CB-61 and 4′-MeO-CB-61 was also concentration dependent: the biotransformation was promoted by a moderate concentration of Cu but inhibited by excess concentrations of Cu. The activities of Cytochrome P450 (CYP450) and S-adenosyl-l -methionine (SAM)-dependent methyltransferase in the roots of rice plants exposed to Cu and CB-61 or its derivatives were consistent with the pattern and trend of the metabolites observed in rice roots. These results could provide valuable insights into the interactions and combined effects of PCBs and heavy metals in plants. Graphical abstract: Image 1 Highlights: Low doses of Cu increased the accumulation of PCB in rice plant. Cu influenced the hydroxylation and methoxylation of PCB in rice. Interconversion between OH-PCB and MeO-PCB was significantly affected by Cu. Cu-triggered root damage and enzyme activity change affected the behavior of PCBs.